Disclosure of Sustainable Development Goals (SDGs) in Bangladesh: A Study on DSE Listed Companies - Saha, Trina; Jannat, Fatema (Asian Business Review, 2021)
Business organizations can secure their future growth by implementing sustainable development goals into their business process. With the advancement in accounting, the nature of reporting practices is also changing. Now reporting is not merely restricted to financial statements, information related to social contribution, environment; sustainability has attained much interest in the corporate world. This study aims to find out the nature and extent of reporting practices of SDGs by some listed companies of the Dhaka Stock Exchange. The samples of this study are 40 companies from several sectors, including banks, pharmaceuticals, insurance, ceramics, telecommunication, etc. are selected based on market volume. Content analysis based on 16 recommendations under governance, strategy, management approach, and performance and targets found from an extensive literature review has been made to fulfill the research objectives. Annual reports from 2019 to 2020 are examined to determine the disclosure issues based on given recommendations. The findings reveal the minimum level of direct disclosure of SDGs but a satisfactory level (around 87.5%) of exposure about the consciousness of SDGs and involvement of SDG in strategy (approximately 63.75%). This study is pioneering because there is very little research about it in our country; thus, it is expected to encourage more research on this subject. JEL Classifications: G10, G38, I38